THE INFLUENCE OF THE INDONESIAN LANGUAGE ON ENGLISH AT THE BILINGUAL SCHOOL SMA TUNAS LUHUR PAITON - Diani, Jeliatut; Tri, Endah; Hamdiah, Magfirotul (Qawwam : The Leader's Writing, 2025)
Language interference frequently occurs in bilingual learning, particularly when students mix elements of their mother tongue into a foreign language. At SMA Tunas Luhur Paiton, which implements a bilingual learning system, students are still found making errors in using English due to the influence of Indonesian, especially in terms of structure, vocabulary, and pronunciation. This study aims to describe the forms of Indonesian language interference in students’ English usage. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model, consisting of three stages: data reduction, data display, and conclusion drawing. The results show four main types of interference: phonological, morphological, syntactic, and lexical. Phonological interference is seen in mispronunciations, morphological interference in the application of Indonesian affixation to English, syntactic interference in sentence structures similar to Indonesian, and lexical interference in the use of Indonesian words or phrases in English utterances. The conclusion indicates that Indonesian language interference remains highly dominant in students’ English usage, highlighting the need for more adaptive and contextual learning strategies to improve their bilingual competence.